Milk and Dairy Products Intake Is Related to Cognitive Impairment at Baseline in Predimed Plus Trial. Issue 7 (5th March 2021) - Muñoz‐Garach, Araceli; Cornejo‐Pareja, Isabel; Martínez‐González, Miguel Ángel; Bulló, Monica; Corella, Dolores; Castañer, Olga; Romaguera, Dora; Vioque, Jesús; Alonso‐Gómez, Ángel M.; Wärnberg, Julia; Martínez, J. Alfredo; Serra‐Majem, Luís; et al.
Abstract : Scope: To examine the association between milk and dairy products intake and the prevalence of cognitive decline among Spanish individuals at high cardiovascular risk. Methods and results: Cross‐sectional analyses are performed on baseline data from 6744 adults (aged 55–75 years old). Intake of milk and dairy products is estimated using a food frequency questionnaire grouped into quartiles. The risk of developing cognitive impairment is based on the Mini‐Mental State Examination (MMSE). A higher prevalence of cognitive decline was found in subjects who consumed more grams. Patients with worse MMSE score (10–24) consumed a mean of 395.14 ± 12.21 g, while patients with better MMSE score (27–30) consumed a mean of 341.23 ± 2.73 g ( p < 0.05). Those subjects with the lower milk consumption (<220 g/day) had a higher MMSE score (28.35 ± 0.045). Higher intake of fermented dairy products was observed in participants with a lower MMSE score (OR 1.340, p = 0.003). A positive correlation was found between the consumption of whole milk and the MMSE score ( r = 0.066, p < 0.001). Conclusions: These findings suggest that greater consumption of milk and dairy products could be associated with greater cognitive decline according to MMSE. Conversely, consumption of whole‐fat milk could be linked with less cognitive impairment in the cross‐sectional study. Abstract : There are controversial results about potential impact that milk and dairy product consumption have on cognitive decline. It is observed that extensive consumption of milk and dairy products is found in those subjects with worse cognitive function. Higher milk and dairy intake were found in participants with lower MMSE scores. Conversely, whole‐fat milk and dairy product intake may play a protective role in cognitive impairment, as higher whole‐fat dairy products had better results in MMSE.